PENINGKATAN PRESTASI BELAJAR PENJAS MELALUI IMPLEMENTASI PENDEKATAN TAKTIS DALAM PERMAINAN BULUTANGKIS KELAS VI S - DADANG KOSWARA (Lembaga Penelitian dan Studi kebijakan MADANI Instutute, 2013)
The problems to be examined in this study were : ( a) How does an increase in student achievement with the implementation of the teaching of the use of the Tactical Approach Badminton Games in Health Physical Education and Sport in Class VI ? ( b ) How does the model of teaching on students' motivation and learning outcomes ? Model tactical approach allows students to recognizes the link between play and play performance enhancement , because it provides an alternative tactical approaches for students to learn technical skills in situations permainan.Tujuan in research is to improve the quality of learning the game of badminton in SDN 05 Morning West Cengkareng , West Jakarta . The method that I use in this study is action research method . The population is students of SDN 05 Morning West Cengkareng , West Jakarta . The sample is first sixth grade students as many as 24 people . Sampling using purposive sampling . The results of data processing increase students' motivation in learning the game of badminton with tactical approaches to improving each cycle . It is seen from the percentage of students. Based on the results of a study conducted by researchers and teachers of physical education , the implementation of a tactical approach to the game of badminton in SDN 05 Morning West Cengkareng , West Jakarta , a special class VI , increased motivation in playing badminton . This is evident from the students' ability to create space , space and maintains winning numbers in playing badminton . It has been proven through the implementation of the Tactical Approach Model badminton game activities can improve students' basic motor skills in the subjects of Physical Education , the effectiveness of the game of badminton for the advancement of science education khusnya scientific field of physical education